Engorde de cachama (Colossoma macropomum) en jaulas flotantes utilizando diferentes poblaciones. Quevedo. - Silva Valdiviezo, Segundo (2012)
The investigative work was carried out in the canton Santa Clara, county of Pastaza, fish in the laboratory of the Municipal Government of the canton Santa Clara, located in the km 46 of the road Puyo-Tena. The present investigation had for object to value the one it puts on weight of cachama (Colossoma macropomum) in floating cages using different populations. The densities were 10 cachamas for m3, 20 cachamas for m3 and 30 cachamas for m3. The field works were carried out under conditions of ambient temperature 230C, 75% of relative humidity, heliophany 960 hours of average yearly and 540 m.s.n.m. The design experimental employee was a D.B.C.A. with 3 treatments and 4 repetitions, the taking of data was made during 60 days, to which were carried out the statistical analysis by means of Statistical Analysis System (SAS). The procedure ANOVA was used for the variance analysis and test of Tukey (0,05). He was also carried out an economic analysis of each treatment in study: Application cost, total entrance, balance of income, relations benefit/cost and production/kg cost................................